Theoretical Exploration and Clinical Application of Moxibustion for Heat Syndrome - 胡玲 蔡荣林 夏晓红 秦黎虹 何璐 龙迪和 (Journal of acupuncture and tuina science, 2008)
This article gives a profound exploration on the theoretical origin, prohibitions and mechanisms of moxibustion for heat syndrome. Based upon the ancient and modern literature, this article also gives a classified summarization on diseases of moxibustion for heat syndrome, in order to obtain a thorough understanding about the theory and clinical application of moxibustion for heat syndrome, hence to further perfect the theory of moxibustion and guide the clinical practice.